Environmental Factors in Affecting Student Entrepreneurship Decision - Agus Eko Sujianto; Mashudi Mashudi; Aliya Khansa (Universitas Muhammadiyah Ponorogo, 2024)
The aim of this research is to examine the influence of environmental factors on students' entrepreneurial decisions in Indonesia. Based on theoretical mapping and previous research, the results showed that the environmental factors in question are the internal and external environment. The research design used is quantitative, with the population consisting of alumni of the Master of Sharia Economics UIN SATU Tulungagung. Based on the distribution of questionnaires to 158 alumni, 123 respondents or 78% were obtained and the remaining 22% did not fill out the questionnaire. By analyzing data using regression, the results showed that there was a significant positive internal and external environment on entrepreneurial decisions. Respondents were motivated to become entrepreneurs because it has been their dream since birth, government policies are pro-entrepreneurship, open access to obtain financing, entrepreneurship has become a culture, and promises independence for an entrepreneur.